Carbetocin for the prevention of postpartum hemorrhage: a systematic review and meta-analysis of randomized controlled trials. (1st February 2016) - Jin, Bohong; Du, Yongming; Zhang, Fubin; Zhang, Kemei; Wang, Lulu; Cui, Lining
Abstract: Objective : To compare the efficacy and safety profile of carbetocin with other uterotonic agents in preventing postpartum hemorrhage. Methods : PubMed, Web of Science, Scopus and EBSCOhost were searched for relevant randomized controlled trials published until September 2013. Results : Carbetocin was associated with a significantly reduced need for additional uterotonic agents (RR = 0.68, 95% CI: 0.55–0.84, I 2  = 4%) compared with oxytocin in women following cesarean delivery. However, with respect to postpartum hemorrhage, severe postpartum hemorrhage, mean estimated blood loss and adverse effects, our analysis failed to detect a significant difference. Studies comparing carbetocin with syntometrine in women undergoing vaginal delivery demonstrated no statistical difference in terms of risk of postpartum hemorrhage, severe postpartum hemorrhage or the need for additional uterotonic agents, but the risk of adverse effect was significantly lower in the carbetocin group. Conclusions : Carbetocin has been associated with a similar low incidence of adverse effects to oxytocin and at least as effective as syntometrine and may become an alternative uterotonic agent for the prevention of postpartum hemorrhage. Further studies should be conducted to determine the safety and efficacy profile of carbetocin in women with cardiac disorders and to analyze the cost-effectiveness and minimum effective dose of carbetocin.